2019
DOI: 10.7358/ecps-2019-019-schl
|View full text |Cite
|
Sign up to set email alerts
|

Soft Skills and European Labour Market: Interviews with Finnish and Italian Managers

Abstract: Gaetano DomeniciEditoriale / Editorial Cinquecentesimo anniversario della morte di Leonardo da Vinci: da celebrazioni di rito, ad occasione per un nuovo sviluppo culturale del Paese

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…A thorough study on the situation regarding demand of soft skills from employers and ability of the employees to fulfil such demand was conducted by Schleutker, Caggiano and Coluzzi in the European labor market (Schleutker et al 2019). In the study involving 64 managers, it has been reported that the significance of soft skills to employers seemed to vary depending on the working environment as well as the field.…”
Section: Soft Skills -Definition and Rationale Behind Continuous Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough study on the situation regarding demand of soft skills from employers and ability of the employees to fulfil such demand was conducted by Schleutker, Caggiano and Coluzzi in the European labor market (Schleutker et al 2019). In the study involving 64 managers, it has been reported that the significance of soft skills to employers seemed to vary depending on the working environment as well as the field.…”
Section: Soft Skills -Definition and Rationale Behind Continuous Demandmentioning
confidence: 99%
“…Since there are various classifications for soft skills available in the academic literature, we have decided to use the soft skill list and classification in accordance with European Skills/Competencies, qualifications and occupations (ESCO): https://ec.europa.eu/esco/portal/skill This classification has been applied by Schleutker et al in the soft skills study conducted for the European Labor Market (Schleutker et al 2019).…”
Section: Soft Skills Used In This Researchmentioning
confidence: 99%
“…This raises an uncomfortable pressure between the advocates of scientific literacy, understood as fundamental knowledge, and those who prefer giving priority to learning professional skills. As Schleutker et al (2019) note, skills and competences are required in an increasingly higher degree by a growing competitive labor market. The controversy inevitably starts when people wonder up to which extent University may have impoverished the conceptual training basis, so as to focus their efforts on employability.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo expuesto, las aptitudes que los futuros ingenieros deben dominar en el aula y desarrollar durante su práctica profesional son principalmente habilidades blandas, pues se trata de comportamientos transferibles que se pueden utilizar en diferentes contextos de la vida (Schleutker et al, 2019), por eso el desarrollo de estas habilidades son importantes y necesarias para afrontar el mercado laboral que es muy exigente y competitivo (Caggiano et al, 2020); también en nuestro país no se ha dado la importancia necesaria a la evaluación y desarrollo de la capacidad espacial, ni en la educación básica ni en la superior por lo que estos cambios son importantes para los futuros ingenieros civiles (Gómez-Tone, 2019).…”
Section: Introductionunclassified